Riİit Dairesel Bir Pançla Bastırılan Ve Elastik Yarım Düzleme Oturan Tabakanın Sürtünmeli Değme Problemi - Çömez, İsa; Erdöl, Ragıp (Teorik ve Uygulamalı Mekanik Türk Milli Komitesi, 2010)
In this study, frictional contact problem for a layer resting on a homogeneous substrate is considered according to the theory of elasticity. The layer is indented by a rigid cylindrical stamp and subjected to concentrated normal and tangential forces. The friction between the layer and the stamp and between the layer and substrate is taken into account. The problem is reduced to a system of singular integral equations in which the contact pressure functions and the contact areas are the unknown by using integral transform technique and the boundary conditions of the problem. The system of singular integral equation is solved numerically by making use of Gauss-Jacobi Integration formula, considering equilibrium and consistency conditions. Numerical results for the contact pressures and the contact areas, are given, in the case of friction and frictionless.

Bu çalışmada elastik yarım düzleme oturan tabakantn sürtünmeli degme problemi Elastisite Teorisine göre çözülmüştür. Tabaka dairesel panç araclılığıyla tekil yükle bastırılırken, pança aynı zamanda yatay bir kuvvet etki ettirilmiştir. Panç ile tabaka ve tabaka ile yarım düzlem arasmdaki sürtünme etkisi dikkate alınmıştır. Problem integral dönüşüm teknigi ve silur şartların kullanılmasıyla degme uzunlukların ve degme gerilmelerinin bilinmeyen oldugu iki tane tekil integral denklemden oluşan bir integral denklem sistemine indirgenmiştir. Tekil integral denklemin sayisal çözümü, denge ve uygunluk sartlarl da dikkate alınarak, GaussJacobi integrasyon formülasyonuyla gerçeklestirilmis, sürtünmeli ve sürtünmesiz durumda degme bölgelerinde olusan degme uzunlukları ve degme gerilmeleri bulunmustur.

Conference Paper -- Theoretical and Applied Mechanical Turkish National Committee, 2010

Konferans Bildirisi -- Teorik ve Uygulamalı Mekanik Türk Milli Komitesi, 2010